Study FTIR and AC Conductivity of Nanocomposite Electrolytes - Swady, Elaaf Ali; Jawad, Mohammed K. (Iraqi Journal of Physics, 2021)
In the present work polymer electrolytes were formulated using the solvent casting technique. Under special conditions, the electrolyte content was of fixed ratio of polyvinylpyrolidone (PVP): polyacrylonitrile (PAN) (25:75), ethylene carbonate (EC) and propylene carbonate (PC) (1:1) with 10% of potassium iodide (KI) and iodine I2 = 10% by weight of KI. The conductivity was increased with the addition of ZnO nanoparticles. It is also increased with the temperature increase within the range (293 to 343 K). The conductivity reaches maximum value of about (0.0296 S.cm-1) with (0.25 g) ZnO. The results of FTIR for blend electrolytes indicated a significant degree of interaction between the polymer blend (PVP and PAN) and the KI salt. From the electrolyte observations of the nanocomposites, the broad peak became narrower after adding the ZnO nanoparticle to the KI salt. The dielectric reaction decreased with the increase of the frequency at room temperature. The high dielectric permittivity of the polymer at lower frequencies can be attributed to the dipoles having sufficient time to get aligned with the electric field, resulting in higher polarization.